The hollow fiber bioreactor as a stroma-supported, serum-free ex vivo expansion platform for human umbilical cord blood cells - Xue, Cao (2015)
The bone marrow microenvironment plays an integral role in the regulation of hematopoiesis. Residing stromal cells and the extracellular matrix in the bone marrow microenvironment provide biological signals that control hematopoietic stem cell (HSC) function. In this study, we developed a bio-mimetic co-culture platform using the hollow fiber bioreactor (HFBR) for ex vivo expansion of HSCs. We evaluated the efficacy of such a platform in comparison to standard cultures performed on tissue culture polystyrene (TCP), using a human stromal cell line (HS-5) as stromal support, co-cultured with lineage-depleted human cord blood cells in serum-free medium supplemented with a cytokine cocktail. Our results showed that the performance of the HFBR in supporting total cell and CD34+ progenitor cell expansion was comparable to that of cultures on TCP. Cells harvested from the HFBR had a higher clonogenic ability. The performance of ex vivo-expanded cells from the HFBR in hematopoietic reconstitution in humanized mice was comparable to that of the TCP control. Scanning electron microscopy revealed that stroma cell growth inside the HFBR created a three-dimensional cell matrix architecture. These findings demonstrate the feasibility of utilizing the HFBR for creating a complex cell matrix architecture, which may provide good in vitro mimicry of the bone marrow, supporting large-scale expansion of HSCs.